2017
DOI: 10.1111/tpj.13771
|View full text |Cite
|
Sign up to set email alerts
|

Alternative polyadenylation is involved in auxin‐based plant growth and development

Abstract: Auxin is widely involved in plant growth and development. However, the molecular mechanism on how auxin carries out this work is unclear. In particular, the effect of auxin on pre-mRNA post-transcriptional regulation is mostly unknown. By using a poly(A) tag (PAT) sequencing approach, mRNA alternative polyadenylation (APA) profiles after auxin treatment were revealed. We showed that hundreds of poly(A) site clusters (PACs) are affected by auxin at the transcriptome level, where auxin reduces PAC distribution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 69 publications
3
40
0
Order By: Relevance
“…S4, A and C). The trends of profiles were similar to those observed in Hong et al (2018). The slight difference in the frequencies of U in auxin-treated samples might be due to differences in durations of the auxin treatments in the two studies.…”
Section: Atcstf77 Affects Poly(a) Site Choicesupporting
confidence: 75%
“…S4, A and C). The trends of profiles were similar to those observed in Hong et al (2018). The slight difference in the frequencies of U in auxin-treated samples might be due to differences in durations of the auxin treatments in the two studies.…”
Section: Atcstf77 Affects Poly(a) Site Choicesupporting
confidence: 75%
“…However, in oxt6, there was a significantly greater increase in the expression of ARF7 and ARF19 when exogenous IAA was applied than that of WT. This further validates the role of CPSF30 in auxin regulation of LRs growth and development to a greater extent through ARF19 [134].…”
Section: Fip1 and Cpsf30-l Regulatory Modulesupporting
confidence: 77%
“…As mentioned above, Cd affects auxin signaling, which seems to involve changes in poly(A) site usage (Hong et al ., ). We found that a significant number of genes involved in auxin signaling were deregulated in fip1‐2 (Table S1e), and some of them displayed differential poly(A) usage (Table S1h).…”
Section: Resultsmentioning
confidence: 97%
“…In Arabidopsis, hypoxia leads to an increased usage of poly(A) sites within coding regions and the 5′‐UTR, affecting their stability and translation (De Lorenzo et al ., ). In addition, APA also seems to be important to maintain correct hormonal signaling, as in the case of auxin (Hong et al ., ). Recently, a T‐DNA insertional mutant in the FIP1 gene has been reported.…”
Section: Introductionmentioning
confidence: 97%